2014
DOI: 10.1530/jme-14-0063
|View full text |Cite
|
Sign up to set email alerts
|

PPAR ligands improve impaired metabolic pathways in fetal hearts of diabetic rats

Abstract: In maternal diabetes, the fetal heart can be structurally and functionally affected. Maternal diets enriched in certain unsaturated fatty acids can activate the nuclear receptors peroxisome proliferator-activated receptors (PPARs) and regulate metabolic and anti-inflammatory pathways during development. Our aim was to investigate whether PPARa expression, lipid metabolism, lipoperoxidation, and nitric oxide (NO) production are altered in the fetal hearts of diabetic rats, and to analyze the putative effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
(67 reference statements)
0
15
0
1
Order By: Relevance
“…Epidemiological studies demonstrate that circulating maternal triglyceride levels independently and temporally correlate with both fetal overgrowth and ventricular hypertrophy in offspring of diabetic mothers (1,19,33,53,56), which suggests a strong lipid-mediated influence. Although previous studies have reported individual effects of maternal diabetes or a HF diet on cardiovascular disease risk (7,13,14,33,35), our study adds evidence that a maternal HF diet in combination with diabetes is especially detrimental for the developing fetal heart. 5.…”
Section: Discussionmentioning
confidence: 51%
“…Epidemiological studies demonstrate that circulating maternal triglyceride levels independently and temporally correlate with both fetal overgrowth and ventricular hypertrophy in offspring of diabetic mothers (1,19,33,53,56), which suggests a strong lipid-mediated influence. Although previous studies have reported individual effects of maternal diabetes or a HF diet on cardiovascular disease risk (7,13,14,33,35), our study adds evidence that a maternal HF diet in combination with diabetes is especially detrimental for the developing fetal heart. 5.…”
Section: Discussionmentioning
confidence: 51%
“…Sex differences in the intrauterine programming of metabolic and cardiovascular diseases have been observed in different experimental models of intrauterine growth restriction, obesity, and diabetes . Experimentally, we have previously demonstrated that diets enriched in 6% olive oil (highly enriched in oleic acid, an unsaturated fatty acid that activates PPARα) are able to regulate lipid‐metabolic pathways as well as oxidative and nitrative pathways in different fetal organs of diabetic rats, including the fetal heart . In this work, we hypothesize that maternal diabetes leads to gender‐dependent alterations in lipid metabolism in the heart of offspring from diabetic rats, and that these alterations are prevented by maternal diets enriched in 6% olive oil.…”
Section: Introductionmentioning
confidence: 85%
“…Damage in the offspring's heart has also been found in severe models of pregestational diabetes . In a pregestational but mild experimental model of diabetes, we have previously found that the fetus accumulates lipids in different fetal organs, including the liver, lung, and heart; organs in which the activation of PPARα regulates the expression of genes involved in lipid metabolism . This mild diabetic model is neonatally induced by streptozotocin, has been thoroughly characterized during pregnancy, and is particularly relevant as its glycemia ranging 150–230 mg/dL resembles the levels of glycemia often seen in human diabetic pregnancies .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…PPAR␥ activation resulted in suppression of placental NO levels (62). Furthermore, in rat offspring exposed to maternal diabetes, PPAR ligands beneficially modulated lipid composition and metabolic enzyme expression in lungs and led to a reduction in NO production and lipoperoxidation in hearts (78,79).…”
Section: Human Perspectivementioning
confidence: 99%